Genome-Wide Target Analyses of Otx2 Homeoprotein in Postnatal Cortex - Sakai, Akiko; Nakato, Ryuichiro; Ling, Yiwei; Hou, Xubin; Hara, Norikazu; Iijima, Tomoya; Yanagawa, Yuchio; Kuwano, Ryozo; Okuda, Shujiro; Shirahige, Katsuhiko; Sugiyama, Sayaka (Frontiers in Neuroscience, 2017)
Juvenile brain has a unique time window, or critical period, in which neuronal circuits are remodeled by experience. Mounting evidence indicates the importance of neuronal circuit rewiring in various neurodevelopmental disorders of human cognition. We previously showed that Otx2 homeoprotein, essential for brain formation, is recaptured during postnatal maturation of parvalbumin-positive interneurons (PV cells) to activate the critical period in mouse visual cortex. Cortical Otx2 is the only interneuron-enriched transcription factor known to regulate the critical period, but its downstream targets remain unknown. Here, we used chromatin immunoprecipitation sequencing (ChIP-seq) to identify genome-wide binding sites of Otx2 in juvenile mouse cortex, and interneuron-specific RNA-seq to explore the Otx2-dependent transcriptome. Otx2-bound genes were associated with human diseases such as schizophrenia as well as critical periods. Of these genes, expression of neuronal factors involved in transcription, signal transduction and mitochondrial function was moderately and broadly affected in Otx2-deficient interneurons. In contrast to reported binding sites in the embryo, genes encoding potassium ion transporters such as KV3.1 had juvenile cortex-specific binding sites, suggesting that Otx2 is involved in regulating fast-spiking properties during PV cell maturation. Moreover, transcripts of oxidative resistance-1 (Oxr1), whose promoter has Otx2 binding sites, were markedly downregulated in Otx2-deficient interneurons. Therefore, an important role of Otx2 may be to protect the cells from the increased oxidative stress in fast-spiking PV cells. Our results suggest that coordinated expression of Otx2 targets promotes PV cell maturation and maintains its function in neuronal plasticity and disease.